Association of Higher Plasma Vitamin D Binding Protein and Lower Free Calcitriol Levels with Tenofovir Disoproxil Fumarate Use and Plasma and Intracellular Tenofovir Pharmacokinetics: Cause of a Functional Vitamin D Deficiency? - Havens, Peter L. (American Society for Microbiology, 2013)
Tenofovir disoproxil fumarate (TDF) causes bone, endocrine, and renal changes by an unknown mechanism(s). Data are limited on tenofovir pharmacokinetics and these effects. Using baseline data from a multicenter study of HIV-infected youth on stable treatment with regimens containing TDF (n = 118) or lacking TDF (n = 85), we measured cross-sectional associations of TDF use with markers of renal function, vitamin D-calcium-parathyroid hormone balance, phosphate metabolism (tubular reabsorption of phosphate and fibroblast growth factor 23 [FGF23]), and bone turnover. Pharmacokinetic-pharmacodynamic associations with plasma tenofovir and intracellular tenofovir diphosphate concentrations were explored among those receiving TDF. The mean age was 20.9 (standard deviation [SD], 2.0) years; 63% were male; and 52% were African American. Compared to the no-TDF group, the TDF group showed lower mean estimated glomerular filtration rates and tubular reabsorption of phosphate, as well as higher parathyroid hormone and 1,25-dihydroxy vitamin D [1,25-OH(2)D] levels. The highest quintile of plasma tenofovir concentrations was associated with higher vitamin D binding protein, lower free 1,25-OH(2)D, higher 25-OH vitamin D, and higher serum calcium. The highest quintile of intracellular tenofovir diphosphate concentration was associated with lower FGF23. Higher plasma tenofovir concentrations were associated with higher vitamin D binding protein and lower free 1,25-OH(2)D, suggesting a functional vitamin D deficiency explaining TDF-associated increased parathyroid hormone. The finding of lower FGF23 accompanying higher intracellular tenofovir diphosphate suggests that different mechanisms mediate TDF-associated changes in phosphate handling. Separate pharmacokinetic properties may be associated with distinct TDF toxicities: tenofovir with parathyroid hormone and altered calcium balance and tenofovir diphosphate with hypophosphatemia and FGF23 regulation. (The clinical trial registration number for this study is NCT00490412 and is available online at http://clinicaltrials.gov/ct2/show/NCT00490412.)